Analisis Kualitas pada Produksi Tahu menggunakan Metode Statistical Quality Control (SQC) - Suparno Suparno; Narto Narto (Universitas Teuku Umar, 2022)
CV. Sumber Rejeki is a home industry that makes tofu, where in its production the company has not conducted a quality analysis. Because quality analysis has not been carried out properly, resulting in very high product defects that occur during production. In this study, the analysis carried out aims to identify what types of damage occur, and provide suggestions for improvements using the Statistical Quality Control (SQC) method. The research data were processed using the Statistical Quality Control (SQC) method with several stages of activity, namely making examination sheets, histograms, making Pareto diagrams, making control charts, and making cause-and-effect diagrams. The results showed that there were three types of defects, namely soft texture, wrong cut, and dirt. Through the Pareto diagram, it is clear that the percentage of damage to the soft texture is 5,116 bj or 38.8%, the second defect is 4.262 bj or 32.3%, and the last or lowest defect is 3,810 bj or 28.9 cut errors. %. Based on the analysis of the cause-and-effect diagram to find the root cause of the problem, it was found that there were four factors that needed to be improved, these factors were workers, machines, raw materials, and methods. Actions that can be taken to reduce product defects are to carry out regular machine maintenance, provide adequate training to workers, improve discipline, carry out good control of soybean raw materials.